Peer Pressure of Publishing or Perishing (PPPP) - Gupta, Divya (Indian Journal of Community Health, 2021)
Researchers create or improvise knowledge by innovating concepts, methods and/or interpretations. Scientific research and scientific writing seem to be inseparable in this modern world for professional existence. Publications are important to give a thrust and positive boost up in your career. Since last decade, research has taken a new horizon. Medical schools and universities frequently use the quantification of publication as the measure of a scholar’s academic competency. Publications are an essential and sometimes the sole criteria considered during recruitments. The numerical value of the published work is taking a leap step ahead of the quality of research. Scholars, who do not have the aptitude of publishing frequently or who focus more on their clinical work and teaching activities to shape up the undergraduates’ and postgraduates’ future, may find themselves out of this professional race. Each individual faculty of the medical institutions is unique research scholar. There is an upcoming trend that unless they pen down their research, they will be undervalued in the academic workplace. This undue “Peer Pressure of Publishing or Perishing” is floating as the new “Catch Phrase” of the professional era.